Design, synthesis, molecular modeling and biological evaluation of novel Benzoxazole-Benzamide conjugates via a 2-Thioacetamido linker as potential anti-proliferative agents, VEGFR-2 inhibitors and apoptotic inducers - Ibrahim H. Eissa; Radwan El-Haggar; Mohammed A. Dahab; Marwa F. Ahmed; Hazem A. Mahdy; Reem I. Alsantali; Alaa Elwan; Nicolas Masurier; Samar S. Fatahala (Journal of Enzyme Inhibition and Medicinal Chemistry, 2022)
A novel series of 2-thioacetamide linked benzoxazole-benzamide conjugates 1–15 was designed as potential inhibitors of the vascular endothelial growth factor receptor-2 (VEGFR-2). The prepared compounds were evaluated for their potential antitumor activity and their corresponding selective cytotoxicity was estimated using normal human fibroblast (WI-38) cells. Compounds 1, 9–12 and 15 showed good selectivity and displayed excellent cytotoxic activity against both HCT-116 and MCF-7 cancer cell lines compared to sorafenib, used as a reference compound. Furthermore, compounds 1 and 11 showed potent VEGFR-2 inhibitory activity. The cell cycle progression assay showed that 1 and 11 induced cell cycle arrest at G2/M phase, with a concomitant increase in the pre-G1 cell population. Further pharmacological studies showed that 1 and 11 induced apoptosis and inhibited the expression of the anti-apoptotic Bcl-2 and Bcl-xL proteins in both cell lines. Therefore, compounds 1 and 11 might serve as promising candidates for future anticancer therapy development.